THE ROLE OF AUTHENTIC VIDEO CONTENT IN ENHANCING FOREIGN LANGUAGE ACQUISITION - Головчун А. А., Абикенова Т. А. (Вестник ЗКУ, 2025)
This article explores the role of authentic video content in enhancing foreign language (FL) acquisition. Authentic videos, such as films, TV programs, and news broadcasts, offer learners exposure to real-world language and cultural insights, fostering the development of listening, speaking, and cultural awareness. This paper highlights the benefits of integrating video content in language instruction, including improved motivation and engagement, and discusses effective strategies for utilizing authentic videos in the classroom. By employing pre-viewing tasks, comprehension activities, and cultural comparisons, teachers can create a dynamic and immersive learning environment that prepares students for real-life communication. Keywords: Authentic video content; foreign language learning; cultural awareness; listening comprehension; speaking skills; motivation; language acquisition; classroom strategies; multimedia in education.